ChemInform Abstract: Keteniminium Ion‐Initiated Cascade Cationic Polycyclization. Issue 15 (April 2015) - Theunissen, Cedric; Metayer, Benoit; Henry, Nicolas; Compain, Guillaume; Marrot, Jerome; Martin‐Mingot, Agnes; Thibaudeau, Sebastien; Evano, Gwilherm
Abstract: A highly efficient keteniminium‐initiated cationic polycyclization is developed.